Etlingera Elatior (Kecombrang Flower) Juice as a Halal Health Beverage - Mazarina Devi; Heri Pratikto; Aji Prasetya Wibawa; Muntholib Muntholib; Nurul Falah Hashim; Tuatul Mahfud (Universitas Negeri Malang, 2023)
The need for halal food and beverage products continuously increases in every country, especially in Indonesia. This condition encourages the guarantees for halal products circulating in the market. The study of Etlingera elatior has been widely carried out, reporting its potential to be used as a health drink. However, until now, there have not been many studies examining Etlingera elatior as a halal product. This study aims to make a halal and rich antioxidant drink from Etlingera elatior. This study used experimental research with a completely randomized design (CRD). The treatment given was the long blanching time of Etlingera elatior with the identical formula. The materials used in this study consisted of ingredients for making Etlingera elatior drinks and chemical analysis materials. The data analysis included the assessment of the alcohol content and antioxidant capacity of Etlingera elatior juice. From the analysis of the alcohol content, it was found that the Etlingera elatior beverage had a negative alcohol content but a high antioxidant capacity which was good for health. The results of the ethanol content analysis on the Etlingera elatior juice with different blanching time (one minute, one minute and a half, and two minutes) was negative, with a qualitative orange color. This study shows that the Etlingera elatior juice beverage has met the quality standards for zinc (Zn) thus, it is safe for consumption. Also, based on the DMRT results, each Etlingera elatior juice formula is significantly different from one another. Therefore, the Etlingera elatior juice is a halal beverage, good for human health. The results of this study have implications for related stakeholders to develop halal beverage products made from Etlingera elatior and serve it as a potential culinary product to be marketed.